2014
DOI: 10.1080/03057925.2014.912796
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in the education system and the reproduction of socioeconomic disparities in voting in England, Denmark and Germany: the influence of country context, tracking and self-efficacy on voting intentions of students age 16–18

Abstract: This article performs exploratory research using a mixed-methods approach (structural equation modelling and a thematic analysis of interview data) to analyse the ways in which socioeconomic disparities in voting patterns are reproduced through inequalities in education in different national contexts, and the role of self-efficacy in this process. The evidence suggests that in Germany and England students with lower socioeconomic status (SES) have lower levels of general self-efficacy, and that this is reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 32 publications
(38 reference statements)
1
24
0
Order By: Relevance
“…Furthermore, in strongly tracked educational systems that are characterized by differentiation in separate school buildings and school organizations, recruitment networks are likely to be formed within schools, making it hard for students in less demanding school types to incorporate supportive norms on political engagement from outside their homogeneous peer group. Also, the study by Hoskins et al (2014) showed marked differences in political outcomes between vocational and academic forms of education. That study, however, did not find stark differences between the three societies that were investigated (Germany, Denmark, and England).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in strongly tracked educational systems that are characterized by differentiation in separate school buildings and school organizations, recruitment networks are likely to be formed within schools, making it hard for students in less demanding school types to incorporate supportive norms on political engagement from outside their homogeneous peer group. Also, the study by Hoskins et al (2014) showed marked differences in political outcomes between vocational and academic forms of education. That study, however, did not find stark differences between the three societies that were investigated (Germany, Denmark, and England).…”
Section: Discussionmentioning
confidence: 99%
“…The other comparative study (Hoskins et al 2014) studied voting intentions of 16-18-year-olds in Germany, England, and Denmark and found that students enrolled in vocational education reported the intention to take part in elections less often than students in the general track. That was the case in all three countries.…”
Section: Introductionmentioning
confidence: 99%
“…Vocational education in the Netherlands is characterised by more school‐based learning than workplace‐based learning, and a clear hierarchy between types of education that leads to a low status for vocational education compared with general education (Cedefop, ). Several studies indicate that a low status for vocational education impedes students’ civic and political participation as measured by club membership and future voting (Cedefop, ; Hoskins et al ., ).…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Finally, the relatively high status of general education and, contrarily, the stigmatisation of vocational education can affect civic and political attitudes (Van Houtte & Stevens, ). As discussed above, vocational education in the Netherlands has a relatively low status compared with general education, and the low status of vocational education is associated with less civic participation or future voting (Cedefop, ; Hoskins et al ., ). It can be expected that the stigmatisation of vocational education could also lead to less development of other dimensions of civic and political engagement.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…The segregation of students is strongly linked to lowered patterns of high school graduation and college enrolment in the US, even after controlling for individual and other school factors (Palardy 2013). The mix of peers in school is linked to these longer-term outcomes but also to wider non-cognitive outcomes such as students' sense of justice , and to civic knowledge (Collado 2014), and subsequent civic engagement (Hoskins et al 2014). …”
Section: Damage Caused By Segregationmentioning
confidence: 99%